Making sense of violence and victimization in health care work: The emotional labour of ‘not taking it personally’ - Funk, Laura (International review of victimology, 2021)
Despite significant impacts on employee health, workplace violence tends to be minimized and normalized by service workers and by organizations, with employees implicitly held culpable for causing aggression through how they manage interactions. Little is known about how workers accomplish minimization and normalization, or how this process might be entwined with the emotional labour of containing difficult emotions. In this paper an emotional labour lens is joined with a social phenomenological approach to analyze in-depth interviews with 26 employees of one multi-unit health care facility in Western Canada. The purpose was to examine health care workers’ emotional and interpretive responses to aggression from patients and families. Through undertaking ‘deep acting’ and maintaining their moral identities, workers contained fear through minimizing and normalizing aggression and contained frustration through acknowledging mitigating circumstances. This involved constructing themselves as victims of misdirected emotions, and patients and families as victims of aging, caregiving, disability, dementia, and/or dying processes. Emotional labour supports organizational interests in ensuring smooth workflows and promoting patient satisfaction and well-being. It involves ambivalence and contradiction and can reproduce discourses detrimental both to workers and to resident care.